Students' Conduct and Disciplinary Integrated System (SCoDIS) for Kemasukan Rekod Pelajar(KRP), Hal Ehwal Pelajar (HEP) and Fakulti Teknologi Maklumat & Sains Kuantitatif / Norkhamsiah Abdul Malik - Abdul Malik, Norkhamsiah (2005)
Nowadays, technologies have been widely used by all types of people around the world to accomplish their tasks. Reflect to that, this study is to find out an appropriate method to develop a prototype in order to assist staflF of Universiti Teknologi MARA (UiTM) to perform their works. Students' Conduct and Disciplinary Integrated System (SCoDIS) is an application that is used for the educational institutions to manage the students' conduct and disciplinary record. The problem of this study is an existence crisis of the functional process that occurred when the function of the previous system could not work accordingly. The intention of this study is to identify the problem encountered and probe the underlying causes that give the negative effect to the existing system. Beside that. Software Requirement Specification (SRS) and Sofbvare Detailed Design (SDD) documentations are produced to develop a fine prototype for replacing the current system. This study focuses on staff of Hal Ehwal Pelajar (HEP), Bahagian Kemasukan Rekod Pelajar (KRP) and Fakulti Teknologi Maklumat dan Sains Kuantitatif (FTMSK) from UiTM main campus, Shah Alam. Seven staffs from the entire three departments were involved in this study as interviewees. The procedures implemented include an interview session, review of related literature and secondary data analysis. Most of the interviewees suggest that the system should be enhanced and upgraded to become more useful and consistent to complete their works. Because of the consequences, SCoDIS have been developed to overcome the previous problem. This system used PHP language and MySQL as a database for storing the information. More over, it is compatible with any operating system platform and designed for the Web-Based system. Finally, I would like to recommend, by adding the complex functionality, it can perform well and have an ability to handle more complicated task.